SYNTHESIS AND PHYSICOCHEMICAL CHARACTERISTICS OF MESOPOROUS ALUMINOSILICATES - Umbetkaliyeva К.M.; Vassilina G.К.; Abdrassilova А.К.; Khaiyrgeldinovа А.R.; Vassilina Т.К.; Zakirov Zh.Y.; Тaliyeva М.Kh.; Kaldybayeva А.К. (Academic Scientific Journal of Chemistry, 2020)
In the article, the synthesis of mesoporous aluminosilicates was carried out according to the developed methods, in which tetraethylorthosilicate Si(OC2H5)4 was used as a source of silicon, secondary aluminum butoxide (sec-BuO)3Al and aluminum triisopropoxide Al(i-OPr)3 were used as aluminum’s sources. The synthesis of mesostructured aluminosilicate is based on the method of copolycondensation of silicon and aluminum sources in the presence of alcohol. Hexadecylamine (HDA, C16H33NH2) was used as a template for the formation of a porous structure. The physicochemical characteristics of the synthesized structured mesoporous aluminosilicates have been studied. It was found that the synthesized materials MAS-1 and MAS-2 possess high specific surface area from 511 to 1170.0 m2 /g. The presence of a mesoporous and ordered structure in the synthesized aluminosilicates is confirmed by the data of low-temperature nitrogen adsorption/desorption, X-ray diffraction and FT-IR. To determine the relative strength of Brønsted and Lewis acid sites on the surface of mesoporous aluminosilicates, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT) of adsorbed pyridine samples was carried out. DRIFT analysis data demonstrated a majority of Lewis acid sites on the surface of the synthesized materials. We are currently studying the possibility of applying these materials as acidic components of bifunctional catalysts for petrochemical processes.